BOVINE BABESIOSIS AND ANAPLASMOSIS: SOME ASPECTS OF THESE DISEASES - MARTINS, JOÃO RICARDO (1995)
In this article, some aspects conceming the biology of "Tick-Borne Diseases", transmitted by the cattle tick Boophilus microplus are discussed. Although bovine babesiosis has been known over a century, the disease remains as a challenge to researchers in many disciplines. The use of chemotherapy and the introduction of live vaccines are measures that control with reasonabble efficiency the problem but do not solve it. lmprovement in the field of babesiosis and anaplasmosis immunology marfe possible to develop some concepts: immunity is not dependent on the presence of the infection, antibodies have an important role in protection, and prevention can be achieved by dead antigenic material. Progress in the understanding of lhe biology of Babesia and Anaplasma species, specially the establishment of in vitro cultures, may contribute to the control of babesiosis and anaplasmosis.